2016
DOI: 10.1002/cb.1585
|View full text |Cite
|
Sign up to set email alerts
|

Choice confidence in the webrooming purchase process: The impact of online positive reviews and the motivation to touch

Abstract: The webrooming purchase process (i.e. searching for information online and then buying the product offline) is the most extended crosschannel shopping behaviour. With the aim of offering a better understanding of this behaviour, this research relies on information processing and uncertainty reduction theories to propose that consumers use the online information to make the offline purchase with a higher degree of confidence. We examine the effects of a previous online interaction with a product on the preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
271
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(300 citation statements)
references
References 77 publications
(160 reference statements)
10
271
0
11
Order By: Relevance
“…First of all, consumers can touch and feel products offline. Touching and feeling products before purchasing gives consumers confidence about their purchase (Flavián, Gurrea, & Orús, 2016) and reduces the resistance consumers feel when they pay for their purchase (Peck & Childers, 2003). Online, on the other hand, contains abundant information consumers have an easy access to (Bhargave, Mantonakis, & White, 2016;Shen, Cai, & Guo, 2016).…”
Section: Information Search For Gift Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, consumers can touch and feel products offline. Touching and feeling products before purchasing gives consumers confidence about their purchase (Flavián, Gurrea, & Orús, 2016) and reduces the resistance consumers feel when they pay for their purchase (Peck & Childers, 2003). Online, on the other hand, contains abundant information consumers have an easy access to (Bhargave, Mantonakis, & White, 2016;Shen, Cai, & Guo, 2016).…”
Section: Information Search For Gift Choicesmentioning
confidence: 99%
“…Consumers who purchase products with high utilitarian quality tend to focus on cognitive aspects such as "economic value for the money, convenience, and time savings" (Overby & Lee, 2006, p. 1161. In this sense, consumers will feel more comfortable searching for information online because online information covers product attributes more effectively (Flavián et al, 2016) with its convenience, rich information, objectivity, and flexibility (Riquelme & Román, 2014). Utilitarian products can be evaluated more effectively online because consumers can easily locate and compare merchants, products, and attributes in a shorter time (Grewal, Gopalkrishnan, Krishnan, & Sharma, 2003;Mathwick, Malhotra, & Rigdon, 2001).…”
Section: Information Search For Gift Choicesmentioning
confidence: 99%
“…Understanding how reviews affect decisions is critical for services such as dining and travel that cannot be experienced prior to consumption (Christodoulides, Michealidou, & Argyriou, ). For physical products, consumers often read reviews online prior to purchasing in the store (Flavián, Gurrea, & Orús, ). Positive online reviews help reduce uncertainty and increase confidence in the in‐store purchase (Flavián et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For physical products, consumers often read reviews online prior to purchasing in the store (Flavián, Gurrea, & Orús, 2016). Positive online reviews help reduce uncertainty and increase confidence in the in-store purchase (Flavián et al, 2016). According to the 2017 Local Consumer Review Survey, 60% of consumers read restaurant reviews, making them one of the top business categories for review impact (BrightLocal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies have shown the relevance of purchasing process behavior in multiple online and offline channels (Flavián, Gurrea, & Orús, 2016;Gerritsen et. al., 2014;Trenz, 2015), there are few academic papers that have systematically developed a specific instrument for measuring CCB and its benefits for the consumer (Gerritsen et al, 2014;Trenz, 2015).…”
Section: Introductionmentioning
confidence: 99%